Educação e leitura dos hipertextos das novas tecnologias na escola pública - Santos, Antonio Carlos Rodrigues dos (2017)
The hypertexts of the new technologies as reading supports are the object of this research. Related to these technologies are the cellular, the tablet and correlates. In this context, we propose two problems, namely: what actions can the teacher develop in order to obtain promising readings from the hypertexts of the new information and communication technologies? Internet research on the student's own mobile device is a meaningful reading action, which emerges as one of the hypotheses. And, what skills can students develop in the digital hypertext approach of these technologies as far as reading is concerned? Another hypothesis is the development of the perceptive-cognitive ability of the immersive reader to predict and anticipate reading among student users of mobile devices. In the general objective, we intend to analyze the process of reading the digital hypertexts of the NTIC between teachers and students. In the specific objectives, we aim to investigate the abilities developed by the students from the recurrent reading in the hypertext of the NICT, as well as to verify possible innovative actions of the teachers in face of the challenges that surround this new modality of reading teaching. The reference is based on the thinking of Santaella (1983, 2001, 2004, 2007, 2012b, 2013), and Lévy (1993, 1996). Of which, among others, were extracted the concepts of hypertext, reading in cyberspace, text and tessitura, virtualization and interactivity, issues that give legitimacy to users of the interface of new technologies are considered readers, especially of the screens. In the whole of the methodology we opted for a proprietary method of the researcher. The analysis is qualitative in order to imply a systematic principle in the light of objective and intelligible criteria given the complexity of the mobile terrain surrounding these technologies. As for the form, it is a participant research in which the researcher observed his own teaching practice. The technique was organized through the collection of open, closed, audio and written questions directed to teachers and students, as well as several reading occurrences on the mobile devices observed by the researcher in the course of his classes. We conclude, among other issues, that Internet research with students' DM is a hypertextual reading action and contributes substantially to a new form of reading teaching. Still in the wake of actions, we find that the most important of these is the action that discusses the concept of reading, since if the concept ends in reading the printed text, all other research actions will be compromised. In the field of abilities developed by the students that process the digital hypertexts, we find, among others, the ability of the immersive reader to follow clues based on the inductive inferences, characteristic of the Internet user detective. The ability to forecast, anticipate reading based on deductive inferences, analogous to the prospective Internet user. The results of the dissertation pointed out the students' DM hypertexts as reading, and, thus, virtualizes / updates the reading.